Openness and Human Capital as Sources of Productivity Growth : An Empirical Investigation from the MENA Countries - Ilham Haouas; Mahmoud Yagoubi (Institute for the Study of Labor (IZA), 2005)
This paper investigates the impact of openness to trade and higher levels of human capital on the economies of some MENA countries. To answer the question: whether either human capital or openness can be shown to cause productivity, we use panel data on 16 countries spanning the 1965 -2000 period. Controlling for fixed effects as well as endogeneity, the results show a significant impact of openness on productivity growth. We find also an effect, significant at the ten per cent level, of the level of human capital on the level of income but no effect on underlying productivity growth. Our preferred estimator combines high and low frequency differences of the data. We discuss reasons why this estimator is well suited for empirical analysis of economic growth.
Keywords: F43; O53; O11; 330; productivity; openness; human capital; growth; panel data; MENA countries; Produktivität; Wirtschaftswachstum; Humankapital; Politik der offenen Tür; Schätzung; MENA-Staaten; Mittlerer Osten; Nordafrika